2018
DOI: 10.1111/lasr.12327
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Correlates of Public Support for Deterrence Reforms and Hot Spots Policing

Abstract: As one approach to prison downsizing and criminal justice reform, scholars recommend altering the nature of policing by reallocating resources toward policing and increasing sentinel patrols and hot spots interventions. Public attitudes toward these reforms are unknown. In the current police crisis, shifting policies in ways disfavored by the public can impact police‐community relations, especially among those disproportionately affected. The current study uses survey data from a nationally representative samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 109 publications
(166 reference statements)
1
7
0
Order By: Relevance
“…Thus, in addition to the practical difficulties of disbanding or defunding the police (Lum et al., 2021), it appears that public support for doing either is not strong. Past research found that although most Black Americans believe officers discriminate on the basis of race (Ramirez, 2015), they also believe policing is a cost‐effective way to control crime and want police patrols (Metcalfe & Pickett, 2018; Saad, 2020). Clearly, however, reforms are needed to reduce racial bias in policing and police mistreatment of civilians.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to the practical difficulties of disbanding or defunding the police (Lum et al., 2021), it appears that public support for doing either is not strong. Past research found that although most Black Americans believe officers discriminate on the basis of race (Ramirez, 2015), they also believe policing is a cost‐effective way to control crime and want police patrols (Metcalfe & Pickett, 2018; Saad, 2020). Clearly, however, reforms are needed to reduce racial bias in policing and police mistreatment of civilians.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority supported precautionary policies that would reduce police patrols—a key component of deterrence (Lum & Nagin, 2017; Nagin, Solow, & Lum, 2015)—or limit officers’ responsiveness to civilians’ calls for assistance. Prior studies have shown that Americans have great faith in the crime‐control benefits of preventive, patrol‐based policing (Metcalfe & Pickett, 2018). Additionally, policing scholars have increasingly called for police to focus less on apprehension and more on crime prevention through focused patrol and service (Lum & Nagin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is possible that the resource reductions or re-allocations explicit in politically salient proposals to reshape policing were perceived as too extreme and potentially threatening to the roles police play in crime control and order maintenance. Fear of crime has occupied a central role as a source of public support for police authority and punitive policy in prior 6 empirical work (e.g., Block, 1971;Costelloe, Chiricos, and Gertz, 2009;Singer, Chouhy, Lehmann, Walzak, Gertz, and Biglin, 2019;Tyler and Weber, 1982), and more recent work has also shown the mass public believes police are a cost-effective source of crime prevention (e.g., Metcalfe and Pickett, 2018). Public opposition to abolition and defunding might therefore be explained by elevated fears of crime during a period that saw both a significant increase in homicides and widespread beliefs that crime was rising.…”
Section: The Relationship Between Public Opinion and Criminal Justice Policymentioning
confidence: 99%